Early Life Access to Polio Vaccines and Declining Disability Rates in India - Mayanka Ambade; Nidhiya Menon; S. V. Subramanian (Institute of Labor Economics (IZA), 2022)
We evaluate the impact of oral polio vaccines on the incidence of disabilities in India, focusing on polio-related disability. Polio was hyperendemic in India even as recently as the early 1990s but the country was declared wild polio virus-free in 2014. Average treatment effects on the treated from difference-in-differences with multiple time period models that condition on time-invariant demographic and socio-economic characteristics reveal that with access to oral polio vaccines in the year of birth, the incidence of any disability, locomotor disability and polio-related disability declined by 61.4%, 57.3% and 55.9%, respectively. We test for pre-trends and estimate alternate specifications that offer support for these results. Heterogeneity analyses show that in general, access to oral vaccines in the year of birth lowers the incidence of disabilities across gender, rural/urban and education stratifications. An exception is low-caste groups where there is some evidence that post-period average ATT rose. The eradication of polio saved a significant number of lives and brought measurable health and economic benefits to the country.
Keywords: I15; I12; I18; O12; J13; J14; 330; polio; locomotor; disability; acute flaccid paralysis; oral polio vaccines; early childhood; difference-in-differences with multiple time period models